Historical records of the blotched stingray Urotrygon chilensis (Urotrygonidae: Myliobatiformes) yield insight into species distribution: the importance of natural history collections to questions of zoogeography. Issue 3 (19th April 2021) - Ehemann, Nicolás Roberto; García-Rodríguez, Francisco Javier; Pequeño, Germán; Thiel, Ralf; De La Cruz-Agüero, José
Abstract : Urotrygon chilensis (Günther, 1872 ) was described based on a single specimen acquired by the British Museum of Natural History, London, from the Johan Cesar Godeffroy Museum in Hamburg. This medium-sized, benthic stingray is found along the eastern Pacific shelf (distance ranging almost 7000 km). During the last century, it has been frequently mentioned in the taxonomy and biogeography of Chile's marine fishes. However, since the original description in 1872, no other record of this species has been reported from Chilean waters. In this study, the historical presence of U. chilensis in Chile was confirmed based on three mature male specimens held at the Zoological Museum of the University of Hamburg (ZMH) collected in Taltal Harbour (Chile) in July 1894. According to the International Code of Zoological Nomenclature guidelines, we propose Taltal Harbour as the type locality of U. chilensis . Additionally, we conduct a historical review to determine how Albert Günther might have obtained the holotype. The discovery of these specimens catalogued in the fish collection at the ZMH is a demonstration of the important role that natural history museums play in documenting biodiversity patterns. The geographical distribution of U. chilensis is extended to the Central Chile marine ecoregion, approximately 1, 500 km southward, from records in available databases. However, 126 years after its last recorded capture off Chile's coast, the historical presence of U. chilensis at such southern latitudes seems to reflect vagrancy in response to weather conditions.